Building on experience Learning from the past to plan for the future - Feldsien-Sudhaus, Inken (Universitätsverlag Göttingen, 2008)
The LIBER Architecture Group reflects on experience of European library building projects from the past twenty years in order to plan the next generation of library buildings. This documentation of recent library building projects accompanies the 14th Seminar of the LIBER Architecture Group, taking place in Budapest and Debrecen (Hungary) 8-12 of April 2008. Most described projects refer to scientific research libraries, however readers will find examples of an archive or public libraries in Amsterdam and Antwerp. Libraries nowadays are spaces to house information resources (and multimedia) but as well places for learning and communication. Recent design of research libraries takes this new usage into account. Therefore examples of »Learning Resource Centers« supporting students during their studies are enclosed.